Novel markers to detect recombinant human insulin‐like growth factor‐I (rhIGF‐I)/rhIGF binding protein‐3 (rhIGFBP‐3) misuse in athletes. Issue 1 (17th February 2016) - Holt, Richard I. G.; Guha, Nishan; Böhning, Walailuck; Bartlett, Christiaan; Cowan, David A.; Sönksen, Peter H.; Böhning, Dankmar
Abstract : Insulin‐like growth factor‐I (IGF‐I) is abused by elite athletes for its metabolic and anabolic effects. We have previously shown that it is possible to detect IGF‐I misuse by measuring serum IGF‐I and procollagen type III amino‐terminal propeptide (P‐III‐NP) but a pilot study suggested measuring IGF‐II, IGF binding protein‐2 (IGFBP‐2) and acid‐labile subunit (ALS) may improve the detection of IGF‐I administration. The aim of the study was to assess this in a randomized controlled trial. Twenty‐six female and 30 male recreational athletes were randomized to 28 days' treatment with placebo or recombinant human (rh)IGF‐I/rhIGF binding protein‐3 (IGFBP‐3) complex (30 mg/day or 60 mg/day), followed by 56 days' washout. IGF‐II, IGFBP‐2 and ALS (women only) were measured using commercial immunoassays. IGFBP‐2 increased and IGF‐II decreased in response to both low and high dose rhIGF‐I/rhIGFBP‐3 in both women and men while ALS decreased in women in response to high dose rhIGF‐I/rhIGFBP‐3. Two days after discontinuing treatment, significant differences remained between the three treatment groups in IGFBP‐2 and IGF‐II, but not ALS. Thereafter there were no significant differences between the three treatment groups in any of the markers. Combining IGF‐I with IGF‐II and/or IGFBP‐2 improved the performance of the test to detect rhIGF‐I/rhIGFBP‐3 administration in both women and men. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The combination of IGF‐I, IGF‐II and IGFBP‐2 may be used to detect IGF‐I misuse in athletes and have advantages over single marker use.